CSS fundamentals. - Montoya, Christian (LiveLessons., 2009)
"Expert Web developer Christian Montoya teaches you CSS2 the right way--hands-on, and step-by-step! These video lessons focus on exactly what you need to know to master new skills fast and put those skills to work immediately"--Resource description page (viewed March 31, 2010).